2015
DOI: 10.1007/s10895-015-1655-5
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Behavior Between Niclosamide and Pepsin Determined by Spectroscopic and Docking Methods

Abstract: The interaction between niclosamide (NIC) and pepsin was investigated using multispectroscopic and molecular docking methods. Binding constant, number of binding sites, and thermodynamic parameters at different temperatures were measured. Results of fluorescence quenching and synchronous fluorescence spectroscopy in combination with three-dimensional fluorescence spectroscopy showed that changes occurred in the microenvironment of tryptophan residues and the molecular conformation of pepsin. Molecular interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 47 publications
(67 reference statements)
0
7
0
Order By: Relevance
“…Generally speaking, for a combined component model, as submodels are different, it is necessary to conduct a comprehensive analysis of the proportion of the combined model. e combined model needs to conduct analysis and simulation based on actual data and select different weight values according to different data feature sets to ensure that the analysis model is more effective [16,17].…”
Section: Fl Time Series Component Model Of Internet Of Thingsmentioning
confidence: 99%
“…Generally speaking, for a combined component model, as submodels are different, it is necessary to conduct a comprehensive analysis of the proportion of the combined model. e combined model needs to conduct analysis and simulation based on actual data and select different weight values according to different data feature sets to ensure that the analysis model is more effective [16,17].…”
Section: Fl Time Series Component Model Of Internet Of Thingsmentioning
confidence: 99%
“…Three-dimensional fluorescence spectroscopy has been extensively used in the recent years as an analytical technique for studying conformational changes in proteins and can provide detailed information about conformational changes in the protein in the presence of a drug. 27,28 If the interaction between the drug and protein alters the conformation of the protein, the peak position of the excitation and emission wavelengths, or the peak intensity of the characteristic peak, will change.…”
Section: Three-dimensional Fluorescence Spectramentioning
confidence: 99%
“…If both H0$$ \Delta {\mathbf{H}}_{\mathbf{0}} $$ and S0$$ \Delta {\boldsymbol{S}}_{\mathbf{0}} $$ are more than zero, this means that hydrophobic interactions are dominant. When H0$$ \Delta {\mathbf{H}}_{\mathbf{0}} $$ is negative and S0$$ \Delta {\boldsymbol{S}}_{\mathbf{0}} $$ is positive, it is suggested that the main driving forces are electrostatic interactions [49]. As shown in Table 2 H0$$ \Delta {\mathbf{H}}_{\mathbf{0}} $$ <0 and S0$$ \Delta {\boldsymbol{S}}_{\mathbf{0}} $$ >0 indicate that the major forces contributing to the interaction of AMX with EB were electrostatic interactions (Figure 9).…”
Section: Resultsmentioning
confidence: 99%
“…If both ΔH 0 and ΔS 0 are more than zero, this means that hydrophobic interactions are dominant. When ΔH 0 is negative and ΔS 0 is positive, it is suggested that the main driving forces are electrostatic interactions[49].S C H E M E 2 Proposed mechanism of reaction for the formation of a non-fluorescence ion-pair complex between AMX and EB T A B L E 1 Stern-Volmer for the reaction of AMX and EB Drug Temperature (K) Stern-Volmer quenching constant. (K sv ) Â 10 3 (L/mol) Correlation coefficient (r) Bimolecular quenching constant (K q ) Â 10…”
mentioning
confidence: 99%